Fusion of alpha-toxin gene, betal-toxin gene and beta2-toxin gene from Clostridium perfringens type C and its immunogenicity - XU Chong-bo; CHEN Xiang-dong; XU Chong-li; PANG Yue; GAO Feng-shan (浙江大学学报. 农业与生命科学版)
In order to construct the good immunogenic α-β1-β2 fusion protein, a 0.95 kb gene fragment from plasmid pETXA1 containing Clostridium perfringens type C alpha-toxin gene was amplified by PCR and it was inserted into recombinant plasmid pETXB1β2 containing 1.65 kb β1-β2 fusion gene, which was cleaved with NcoI and processed with alkaline phosphatase. The recombinant plasmid pETTXAB1B2 containing 2.6 kb α-β1-β2 fusion gene was constructed and then transformed into Escherichia coli BL21 (DE3) by DNA recombination technique. The recombinant expression plasmid pETXAB1B2 was further studied by restriction endonucleases analysis and nucleotide sequencing. The results show that the recombinant expression pETXAB1B2 possessed a positive α-β1-β2 fusion gene sequence and reading frame. BL21 (DE3) (pETXAB1B2) could produce α-β1-β2 fusion protein and the expressed products were recognized by alpha-toxin, beta1-toxin and beta2-toxin antibodies with ELISA and Western blot analysis. The optimum IPTG induction conditions for the α-β1-β2 fusion gene expression were as follow: culture medium pH 7.5, 37 ℃, and the recombinant strain growth density OD600 at 1.0, and 0.4 mmol·L-1 IPTG for 5 h. The expression level of the α-β1-β2 fusion proteins was about 31.2% of total cellular protein with IPTG induction. More importantly, a mouse immunization with crude preparation containing the a-β1 -β2 fusion protein inclusion bodies or inactivated recombinant strain could induce protection against at least 1MLD of the toxin challenging from Clostridium perfringens type C. It is indicated that the constructed recombinant strain BL21 (DE3) (pETTXAB1B2) can be used as a candidate of vaccine strain.